2019
DOI: 10.1097/rlu.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of 18F-Prostate-Specific Membrane Antigen-1007 and 18F-Fluorocholine PET/CT in Biochemically Relapsed Prostate Cancer

Abstract: Purpose of the Report The aim of the study was to prospectively compare performance of 18F-fluorocholine (FCH) and 18F-prostate-specific membrane antigen (PSMA)-1007 PET/CT in patients with biochemical relapse (BCR) of prostate cancer and low prostate-specific antigen levels. Methods We prospectively enrolled 40 BCR patients after radical treatment and prostate-specific antigen levels 2.0 ng/mL or less. 18F-FCH and 18F-PSMA-1007 PET/CT imaging was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 14 publications
5
28
0
1
Order By: Relevance
“…They found that PSMA PET/CT showed higher detection rates and should be the tracer choice when PET/CT imaging is considered for patients with biochemical recurrence after radical prostatectomy with low PSA concentrations (≤2.0 ng/ml). The same conclusion was drawn from another prospective study paired that compared 18 F-PSMA and 18 Ffluorocholine PET/CT in patients with BCR (42). The advantage of PSMA-targeted PET/CT imaging could be attributed to the high expression of PSMA in PCa and its metastases.…”
Section: Discussionsupporting
confidence: 58%
“…They found that PSMA PET/CT showed higher detection rates and should be the tracer choice when PET/CT imaging is considered for patients with biochemical recurrence after radical prostatectomy with low PSA concentrations (≤2.0 ng/ml). The same conclusion was drawn from another prospective study paired that compared 18 F-PSMA and 18 Ffluorocholine PET/CT in patients with BCR (42). The advantage of PSMA-targeted PET/CT imaging could be attributed to the high expression of PSMA in PCa and its metastases.…”
Section: Discussionsupporting
confidence: 58%
“…The majority of studies of retrospective design do not describe how results of the index test are interpreted separate to the reference test, pre-defined reference standards, or whether all patients were included in the analysis. Semi-quantitative standardized uptake values (SUV) were reported by only seven studies [ 4 , 26 , 28 , 30 , 31 , 33 , 34 ], and definition of uptake (SUVmax/SUVmean, thresholds and definition) was heterogeneously reported. Only one study reports diagnostic accuracy data [ 4 ], and two studies used a defined reference standard for lesion confirmation or interpretation [ 4 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…18 for 18 F-Flurocholine. 46 Lesions detected by both agents in this study had a significantly higher standardized uptake value (SUV) for 18 F-PSMA-1007 than 18 F-Flurocholine. 46 These studies support PSMA-PET imaging as superior to 18 F-labelled choline derivatives in the biochemically recurrent prostate cancer setting.…”
mentioning
confidence: 61%
“…A study which directly compared 68 Ga‐PSMA‐11 vs 18 F‐Fluromethylcholine PET/CT in 38 prostate cancer patients with BCR (mean PSA 1.74 ± 2.54 ng/mL) after curative treatment demonstrated a detection rate of recurrent lesions of 66% for 68 Ga‐PSMA‐11 vs 32% for 18 F‐Fluromethylcholine 45 . A study which compared 18 F‐PSMA‐1007 vs 18 F‐Flurocholine PET/CT in 40 prostate cancer patients with a BCR (PSA <0.2 ng/mL), demonstrated a detection rate of recurrent lesions of 60% for 18 F‐PSMA‐1007 vs 5% for 18 F‐Flurocholine 46 . Lesions detected by both agents in this study had a significantly higher standardized uptake value (SUV) for 18 F‐PSMA‐1007 than 18 F‐Flurocholine 46 .…”
Section: Psma Pet Vs Metabolic Pet Imaging Agents For Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation